2018
DOI: 10.1007/s13762-018-2043-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel adsorbent from sago-grafted silica for removal of methylene blue

Abstract: Eco-friendly and low-cost adsorbent prepared from sago waste was investigated for the removal of methylene blue. Sago "hampas," an abundant waste from sago industries, was transformed into activated carbon followed by chemical grafting with silica from activated rice husk in the presence of 3-(triethoxysilyl)-propylamine to afford sago-grafted silica 80:20 (wt/wt%) and 50:50 (wt/wt%). The physicochemical properties of the adsorbents were characterized, and their effectiveness in removing methylene blue was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a previous study, the same adsorption kinetic trends were observed for the synthesis of nano-silica-coated magnetic carbonaceous adsorbents for the adsorption of MB in water using a lowtemperature hydrothermal carbonization technique (HCT), indicating that the adsorption of MB by PSAM is controlled by multiple processes and not by a single process [13,35]. Activated lignin-chitosan extruded pellets (ALiCE) 36.25 [4] Carboxymethyl chitosan-modi ed magnetic-cored dendrimers (CCMDs) 96.31 [37] Mesoporous silicon carbon (MSC) 156.56 [38] Magnetic starch-based composite hydrogel microspheres (SCHMs) 88.33 [39] Hydrophobic (surface modi ed) silica aerogel (MSA) 65.74 [40] Paintosorp 44.64 [41] Sago-grafted silica 80:20 10.31 [42] PSAM 90.01 This work 3 shows the parameters of the adsorption isotherm t. From the data of the graphs, it can be seen that the R 2 of the Langmuir model is close to 1, so the Langmuir model is more applicable to the adsorption of PSAM on MB [43]. The Langmuir model applies to the adsorption of the monomolecular layer, so the adsorption of PSAM on MB is of monomolecular layer adsorption.…”
Section: Adsorption Of Mbmentioning
confidence: 99%
“…In a previous study, the same adsorption kinetic trends were observed for the synthesis of nano-silica-coated magnetic carbonaceous adsorbents for the adsorption of MB in water using a lowtemperature hydrothermal carbonization technique (HCT), indicating that the adsorption of MB by PSAM is controlled by multiple processes and not by a single process [13,35]. Activated lignin-chitosan extruded pellets (ALiCE) 36.25 [4] Carboxymethyl chitosan-modi ed magnetic-cored dendrimers (CCMDs) 96.31 [37] Mesoporous silicon carbon (MSC) 156.56 [38] Magnetic starch-based composite hydrogel microspheres (SCHMs) 88.33 [39] Hydrophobic (surface modi ed) silica aerogel (MSA) 65.74 [40] Paintosorp 44.64 [41] Sago-grafted silica 80:20 10.31 [42] PSAM 90.01 This work 3 shows the parameters of the adsorption isotherm t. From the data of the graphs, it can be seen that the R 2 of the Langmuir model is close to 1, so the Langmuir model is more applicable to the adsorption of PSAM on MB [43]. The Langmuir model applies to the adsorption of the monomolecular layer, so the adsorption of PSAM on MB is of monomolecular layer adsorption.…”
Section: Adsorption Of Mbmentioning
confidence: 99%
“…The results showed a highly significant surface area difference between untreated and treated biochar. The large surface area of SAC was due to the larger pore size of SAC (Rajan et al, 2019). The surface area of SAC is highly dependent on the carbonization temperature with a higher temperature giving larger surface areas (Hu & Srinivasan, 1999).…”
Section: Instrumental Analysismentioning
confidence: 99%